PERTUMBUHAN PENDUDUK DAN STRUKTUR LAPANGAN PEKERJAAN DI JAWA TENGAH - Hardati, Puji (Forum Ilmu Sosial, 2013)
The purpose of this research is to analyze the population growth and employment structure in Central Java. The analysis showed that during the last five decades the population growth rate in Central Java has experienced significant decrease. Although the growth rate has decreased to account for less than one percent each year, it is still an increase in open unemployment. The population residing in the village on the wane. Employment in the agricultural sector in rural areas there is a tendency increasingly unattractive labor force. Decade-long decline in the number of people working in agriculture decreased by almost 7 percent. Contribution of agriculture to the gross regional domestic product decreased to 19.85 percent